2019
DOI: 10.1017/s0272263119000226
|View full text |Cite
|
Sign up to set email alerts
|

How Do Second Language Listeners Perceive the Comprehensibility of Foreign-Accented Speech?

Abstract: The current study examines how second language (L2) users differentially assess the comprehensibility (i.e., ease of understanding) of foreign-accented speech according to a range of background variables, including first language (L1) profiles, L2 proficiency, age, experience, familiarity, and metacognition. A total of 110 L2 listeners first evaluated the global comprehensibility of 50 spontaneous speech samples produced by low-, mid-, and high-proficiency Japanese speakers of English. The listeners were categ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 43 publications
(63 reference statements)
1
17
0
Order By: Relevance
“…Alternatively, it might arise because people often misattribute their assessment of ease or difficulty to an irrelevant source (Greifeneder et al, 2011), which, in this case, amounts to speakers upgrading their partner's comprehensibility based on their own participation in dialogue. Regardless of its source, this self-oriented influence on partner comprehensibility in interaction represents a novel contribution to existing work, which to date has chiefly targeted individual differences in raters' cognitive and experiential profiles (e.g., Saito et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, it might arise because people often misattribute their assessment of ease or difficulty to an irrelevant source (Greifeneder et al, 2011), which, in this case, amounts to speakers upgrading their partner's comprehensibility based on their own participation in dialogue. Regardless of its source, this self-oriented influence on partner comprehensibility in interaction represents a novel contribution to existing work, which to date has chiefly targeted individual differences in raters' cognitive and experiential profiles (e.g., Saito et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The discrepancy here indicates a necessity of generalization of the findings in order to forward L2 speech research to examine potential listener-oriented effect on segmental correlates of L2 comprehensibility. We strongly call for future studies which will carefully examine the complex relationship between different types of segmental features, different groups of listeners and L2 comprehensibility judgments while elaborating a controlled design (see Saito et al, 2019b). Second, although the current study employed two different tasks to elicit L2 speech, contribution to an ongoing discussion of task effect on L2 production (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…It showed that shadowing various Englishes with the occasional use of scripts for a short period is effective for Japanese EFL learners in adapting their perception to an unfamiliar accent. As Saito et al (2019)…”
Section: Discussionmentioning
confidence: 99%
“…Essentially, L1 and non-L1 listeners listen differently (Cutler, 2012). When listening to accented English, L1 listeners' judgment of comprehensibility is different from that of L2 listeners, in that pronunciation accuracy is a crucial factor for L1 listeners, while multiple factors (e.g., pronunciation, fluency, lexicogrammar) are crucial for L2 listeners (Saito et al, 2019). Thus, letting non-native listeners merely listen to English cannot improve their listening comprehension, let alone that of unfamiliar English variations.…”
Section: Listening Instruction For English Learnersmentioning
confidence: 98%